A cooperative formation‐based collision avoidance approach for a group of autonomous vehicles. (12th May 2015) - Yang, Aolei; Naeem, Wasif; Fei, Minrui; Tu, Xiaowei
Summary: This paper employs a unique decentralised cooperative control method to realise a formation‐based collision avoidance strategy for a group of autonomous vehicles. In this approach, the vehicles' role in the formation and their alert and danger areas are first defined, and the formation‐based intra‐group and external collision avoidance methods are then proposed to translate the collision avoidance problem into the formation stability problem. The extension–decomposition–aggregation formation control method is next employed to stabilise the original and modified formations, whilst manoeuvring, and subsequently solve their collision avoidance problem indirectly. Simulation study verifies the feasibility and effectiveness of the intra‐group and external collision avoidance strategy. It is demonstrated that both formation control and collision avoidance problems can be simultaneously solved if the stability of the expanded formation including external obstacles can be satisfied. Copyright © 2015 John Wiley & Sons, Ltd.